Effects of Germination Duration on the Nutrient Content, and Functional and Sensory Attributes of Whole Wheat Bread Made from Organic Hard Red Wheat. (29th May 2020) - Stern, Alexandra; Berstein, Julia; Jones, Stephen; Blumberg, Jeffrey; Griffin, Timothy
Abstract: Objectives: It has been previously suggested that bread made from germinated grains have superior nutrient profiles, sensory attributes, and/or functional characteristics. This study assessed the impact of germination duration on two organic wheat varieties (Expresso and Basalt; Triticum aestivum L.). The outcomes of interest were wheat nutrient content, dough functional characteristics, and bread sensory attributes. We hypothesized that free sugar and resistant starch content would increase with germination duration and phytic acid, total starch, and solubilized starch would decrease. We hypothesized that functional characteristics of dough would worsen with greater germination duration and sensory perceptions of bread would follow a similar trend. Methods: Each wheat variety was tested at four different germination durations (6, 12, 24, and 36 h) and compared to a control ungerminated wheat (0 h). Free sugar, starch, and phytic acid content were determined enzymatically. Dough functionality was assessed using the falling number and farinograph results. A semi-trained panel of judges assessed the sensory characteristics of the resulting whole-wheat bread. Results: The free sugar content of wheat flour increased with germination duration ( P <   0.05). Only in Expresso, total and solubilized starch decreased after a 24-h germination period ( P <   0.05). No clear pattern emerged for changes in resistant starch or phytic acid. Functional characteristics decreased with germination duration and resulted in whole-wheat bread with inferior crumb in the 24-h (Expresso) and 36-h (Basalt) treatments ( P <   0.05). Despite inferior functionality in longer germination durations, there was no difference in the overall sensory acceptability of breads. This suggests that the use of germinated wheat in artisanal bread would be acceptable to consumers. Conclusions: We observed a positive linear relationship between germination duration and free sugar content. This result suggests that breads made from wheat germinated for greater than 24-h may be sweeter and lead to greater acceptance of whole-wheat bread. Funding Sources: We would like to acknowledge the educational gifts provided to the Tufts Friedman School of Nutrition Science and Policy from Skagit Valley Malting and Cascade Organic Farms.